A sibling based design to quantify genetic and shared environmental effects of venous thromboembolism in Sweden. Issue 149 (January 2017) - Zöller, Bengt; Ohlsson, Henrik; Sundquist, Jan; Sundquist, Kristina
Abstract: Introduction: Few large studies have examined the heritability of venous thromboembolism (VTE). Moreover, twin studies have been suggested to overestimate heritability. The aim of the present study was to determine the heritability nationwide in the general Swedish population using full siblings and half-siblings. Methods: VTE was defined using the Swedish patient register. Full sibling (FS) and half-sibling (HS) pairs born 1950–1990 were obtained from the Swedish Multi-generation Register. A maximum of 5 years age difference was allowed. We also required that the individuals within the pair should reside in the same household for at least 8 years or not at all (0 years) before the youngest turned 16. Information about sibling pair residence within the same household, small residential area, and municipality was obtained from Statistics Sweden. We assumed three potential sources of liability to VTE: additive genetic (A), shared (or common/familial) environment (C), and unique environment (E) components. Results: Totally 881, 206 FS pairs and 95, 198 HS pairs were included. The full model predicted heritability for VTE with 47% for males and 40% for females. Environmental factors shared by siblings contributed to 0% of the variance in liability for both sexes, and unique environment (E) components accounted for 53% in males and 60% in females. Conclusion: The high heritability of VTE risk indicates that genetic susceptibility plays a substantial role for VTE in the Swedish general population. Overestimation of heritability from twin studies is not likely. The proportion of the variance attributable to shared familial environment factors is small. Subject codes: Genetics, epidemiology, thrombosis, cardiovascular disease, embolism Highlights: Few large studies have examined the heritability of venous thromboembolism (VTE). Twin studies have been criticized to overestimate the heritability. The heritability of VTE in Sweden was estimated using a sibling design. The heritability for VTE was 47% for males and 40% for females. Genetic susceptibility of VTE plays a substantial role in the Swedish population.